Penerapan Teknik Self Management Dalam Mengurangi Tingkat Perilaku Agresif Siswa - salmiati, salmiati (STKIP Andi Matappa, 2018)
This study aims to determine the application of self-management techniques to reduce the aggressive behavior of students in public senior high school 1 Segeri. This research uses experimental method, with One-Group Pretest-Posttest Design research design, with a population of 298 students scattered from all classes X public senior high school 1 Segeri and sample research as many as 30 students using the sampling